Penetapan Kadar Beta Karoten pada Daun Sirih Hijau (Piper Betle L.) Berdasarkan Ketinggian Tempat Tumbuh - Dedi Nofiandi; Hazli Nurdin; Sulha Ananda Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Research has been conducted on determining beta carotene levels in green betel leaves (Piper betle L.) based on the altitude at which they grow. The purpose of this study was to determine the levels and differences in beta carotene levels in green betel leaves based on the altitude where it grows. This research consists of qualitative analysis and quantitative analysis. Qualitative analysis with thin layer chromatography and phytochemical screening tests on the extract, while quantitative analysis with UV-Visible spectrophotometry. The results of qualitative analysis with thin layer chromatography showed that green betel leaf extract contains beta carotene compounds obtained Rf value 0.48 and pure beta carotene Rf value 0.48. Other qualitative analysis with phytochemical screening tests on the three sample acetone extracts originating from the Alahan Panjang, Solok and Pasir Jambak areas contained terpenoid, phenolic, flavonoid compounds and did not contain saponin and alkaloid compounds. The results of quantitative analysis obtained the maximum absorption wavelength of beta carotene is 481 nm with the average beta carotene content in green betel leaves of Alahan Panjang, Paninggahan, Solok Regency, and Pasir Jambak respectively, namely 113.845 mg/100 g, 129.98 mg/100 g, and 7.530 mg/100 g. Data analysis using the One Way Anova test (SPSS 31.0) showed a significant effect of the height of the growing area on the beta carotene content of green betel leaves (P < 0.05).